Germinação de sementes de pinho-cuiabano sob deficiência hídrica com diferentes agentes osmóticos - Braga, Lúcia Filgueiras; Sousa, Marcflio Pereira; Cesaro, Alexsandra dos Santos; Lima, Giuseppina Pace Pereira [UNESP]; Gonçalves, Antonio Natal (My University, 2008)
The species Schizolobium amazonicum (Huber ex Ducke) commonly known as pinho-cuiabano or paricá, is one of the trees in Amazonian area used for plantings in degraded areas, reforestations and agroforestry systems. The present work evaluated the germinative behaviour of seeds of Schizolobium amazonicum in relation to the hydric stress, defining their levels of tolerance to those limitations in the environment. The seeds were collected from 30 trees in Alta Floresta-MT and submitted the dormancy treatment by submersion into water at 100°C for 1 minute; followed by treatment with fungicide Ridomil and Cercobin 0,25% each, then being left to germinate in a BOD camera at 30°C under a photoperiod of 12 hours. For evaluating the effect of different water potentials in the germinative process, polyethylene glicol (PEG 6000) was used and the salts NaCI and CaCl 2 used to simulate saline stress. The seeds were put to soak in potentials of 0 (control); -0.1 ; -0.2; -0.3; -0.4 and -0.5MPa. For each treatment 5 repetitions of 20 seeds were used in gerbox, placed between filter paper moistened with 20 mL of PEG, NaCI and CaCl 2 solutions. The solutions were changed at intervals of 24 hours for maintenance of the potential. The evaluations of percentages and germination speed were carry out daily for 8 days, being considered germinated the seeds that presented a 2mm root extension or longer. The data were submitted to analysis of variance and averages compared by the Tukey test at 5% probability. It was concluded that osmotic potentials between -0.4 and -0.5MPa inhibited the germination of seeds of Schizolobium amazonicum completely. The osmotic stress caused by CaCl 2, and PEG injured the germination more than did the stress caused by NaCl.
Seed germination of pinho-cuiabano under water stress by different osmotic agents
Keywords: Forest seed; Osmotic potential; Paricá; Salt tolerance; Schizolobium amazonicum; Agroforestry systems; Alta Floresta; Evaluating; Filter papers; Hydric stresses; Osmotic agents; Osmotic potentials; Osmotic stresses; Plantings; Saline stresses; Seed germinations; Water potentials; Water stresses; Calcium chloride; Forestry; Osmosis; Plants (botany); Polyethylene glycols; Reforestation; Regression analysis; Revegetation; Risk assessment; Seed; Sodium chloride; Water treatment; Agricultural products; Calcium Chloride; Plants; Polyethylene Glycol; Regression Analysis; Risk Assessment; Seeds; Sodium Chloride; Water Treatment